Chill sensitiveness and thermal analysis parameters relationship in hypo-eutectic, Ca and Ca-La inoculated commercial grey cast irons - Stefan E.; Chisamera M.; Riposan I. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Previous experiments showed a specific distribution of Al, La, and Ca on the section of complex (Mn,X)S compounds, found as major nucleation sites for graphite flakes in low-S cast irons (< 0.03%S), and a possible contribution of La to improve their capacity to nucleate graphite, avoiding carbides formation. In the present work, standard thermal [cooling curves] investigations were undertaken to explore Ca and La-Ca bearing FeSi alloys inoculation effects [10 measurements for each inoculant], in 3.7 – 3.8%CE and optimum S and Mn relationship [0.046 – 0.056%S, (%Mn) x (%S) = 0.024 – 0.029]. Representative temperatures on the cooling curves and under-cooling degrees referring to the meta-stable eutectic temperatures were determined and correlated with the chill [carbides/graphite formation sensitiveness], in different solidification conditions [cooling modulus, wedge shape castings, resin sand mould]. Supplementary addition of La to Cabearing inoculants had limited, but specific benefits in these cast irons: lower eutectic recalescence and maximum recalescence rate, higher GRF1 and lower GRF2 graphitizing factors, and lower value of the first derivative at the end of solidification. Consequently, it resulted in a premise for lower shrinkage sensitiveness and lower chill (carbides) sensitiveness, especially at the highest solidification cooling rate (thin wall castings).